Relationship Between Gender and Development Status in Children - Farri Soleimani; Zahra Bajalan; Hamid Alavi Majd; Somayeh Fallah (University of Social Welfare and Rehabilitation Sciences, 2018)
Objective Developmental and behavioral problems are the most prevalent problem in pediatrics after infection and trauma. These problems can be affected by numerous factors. A range of factors is involved in behavior and development problems. Developmental problems have a massive impact on children’s health and eventually have broader scale effect on society. Because of the necessity for more and different follow-ups in children with developmental disorders in the early years of lifetime, determination of effective factors is essential in any society. Therefore, the current study was conducted with a purpose to determine the relationship between gender and developmental status in children. Materials & Methods This is a descriptive design study, performed in 12-month-old children (n=250) who were referred to health services centers affiliated to Qazvin University of Medical Sciences in 2012. Sampling was performed using a multistage method. The data gathering tool included information form and Age and Stages Questionnaire for measuring developmental status. Once parental consent was obtained, the developmental status of the children was measured in five areas, i.e., motor (gross and fine motor skills), problem-solving, personal-social skills and communication. Age and Stages Questionnaire consists of 19 questionnaires at the age of 4-60 –month old with the aim of separating inactive children from further developmental studies of healthy children. Completion of the questionnaire takes 10 to 15 minutes, and it takes about one minute to score. The validity and reliability of the Age and Stages Questionnaire have been reported in various previous studies. The data were analyzed using SPSS software version 18. In this study, statistical analyses were performed using descriptive and inferential statistics. Logistic regression model was used to determine the relationship between gender and developmental status. A P value of ˂0.05 was considered statistically significant. Results The prevalence of developmental delay was 22.4 % (CI 95%: 17–28) in children and the highest prevalence was in the area of communication (8%; CI 95%: 5–11) and the lowest was in the area of problem-solving (2%; CI 95%; 0–4). 39 boys (69.6%) were in the group of developmental delay, and 102 boys (52.6%) were in normal developmental group. To check the status of development difference between groups were used chi-square test showed a significant difference between the two groups. Therefore, developmental delay is significantly higher in boys (P=0.02). By importing the variable studied in the logistic regression model, the male gender variable (P=0.055, OR=0.52) had a significant relationship with a developmental delay of children. Children with suspected developmental disorders in evolution children with normal development, chance of developmental delay in boys 0.52 times more than girls. The other variables (age, education, and occupation of parents, previous history of abortion, type of delivery, parity, spacing between births, weight and head circumference at birth and 12 months of age) did not show a significant relationship with developmental delay.  Conclusion The leading causes of developmental disabilities remain unknown. It seems that gender is one of the causes of developmental delay. In this study, male gender was a factor that is associated with developmental delay. According to the incidence of developmental delay and its effect on society, it is essential that health professionals, with family, and community, monitor the development of children. Identifying the children at risk as soon as possible for diagnosis, earlier intervention, and reduced problems is essential in the future. Further studies are required to confirm the results.